The Role of Blockchain Technology in Enhancing Transparency and Trust in Industrial Relations Negotiations - Muhammad Junaid Kamaruddin; Noverina Silalahi (MJK PUBLISHER, 2024)
The Industrial Revolution 5.0 has brought about a new era in industrial relations, but there are concerns regarding transparency and trust in the negotiation process. Penulis suggests that blockchain technology can address these concerns by enhancing trust and transparency. By utilizing smart contracts, blockchain can increase transparency and security in negotiations with minimal transaction costs. Furthermore, data stored on a blockchain network is difficult to manipulate without authorized authority, thus ensuring the integrity of the system. The researcher use qualitative methods to explain complex subjects, include multiple sources and perspectives, and identify patterns. The application of blockchain technology has already demonstrated increased transparency and trust in supply chain management and can also be extended to industrial relations negotiations. However, further research is needed to fully understand its potential benefits and challenges. To maximize the advantages of blockchain technology, it is recommended to educate the public about its benefits, establish sensible regulations to address security and privacy concerns, and foster collaboration between industry and government to develop consistent standards and a widely accepted framework for blockchain implementation.